Exploring the Interaction between Transportation Infrastructure and Population Dynamics : A Systematic Literature Review - Chung, I Re; Kim, Euijune (Journal of Korea Planning Association, 2025)
This study systematically reviews 28 peer-reviewed journal articles to examine the interaction between transportation infrastructure and population dynamics. The findings reveal that the effects of transportation infrastructure provision vary by type and regional context, falling into two dominant patterns: the Win-Win effect, where transportation infrastructure development stimulates population growth across all affected areas, and the Win-Lose effect, where it fosters population growth in some areas while causing declines in others. Both road and rail infrastructure exhibit these patterns. Roads generally promote population growth, especially in small and remote cities; local roads often show the Win-Win effect, whereas highways enhance accessibility but also induce suburbanization and population dispersion, reflecting the Win-Lose effect. Rail demonstrates the Win-Win effect in less developed regions but fosters suburbanization and gentrification in urbanized areas. High-speed rail often amplifies the siphon effect, facilitating population outflows to major cities with an inverted U-shaped distance effect, representing Win-Lose dynamics. By contrast, airports and seaports consistently exhibit the Win-Win effect, serving as regional growth poles that enhance connectivity and support long-term development. Some studies also identify a bidirectional causal relationship, where population growth drives transportation infrastructure expansion, although mismatches between infrastructure supply and demographic demand are also noted. These findings underscore the need for regionally tailored long-term transportation infrastructure strategies that integrate demographic and economic indicators to more precisely evaluate their impacts. KCI Citation Count: 0